2019
DOI: 10.1007/s00127-019-01774-y
|View full text |Cite
|
Sign up to set email alerts
|

Immigrants’ mental health service use compared to that of native Finns: a register study

Abstract: Purpose Many aspects related to migration might predispose immigrants to mental health problems. Yet immigrants have been shown to underuse mental health services. The aim of this study was to compare the intensity of psychiatric care, as an indicator of treatment adequacy, between natives and immigrants living in Finland. Methods We used nationwide register data that included all the immigrants living in Finland at the end of 2010 (n = 185,605) and their matched controls. Only those who had used mental health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 43 publications
3
16
0
2
Order By: Relevance
“…In the Danish context specifically, significantly less use of psychiatric services has been documented among refugee boys and girls compared with Danish‐born children (50). Similar patterns have been observed in Norway (46) and Finland (51) among young refugees and immigrants. In Sweden, a study also found lower use among children whose parents originated from lower‐ and middle‐income countries (48).…”
Section: Discussionsupporting
confidence: 81%
“…In the Danish context specifically, significantly less use of psychiatric services has been documented among refugee boys and girls compared with Danish‐born children (50). Similar patterns have been observed in Norway (46) and Finland (51) among young refugees and immigrants. In Sweden, a study also found lower use among children whose parents originated from lower‐ and middle‐income countries (48).…”
Section: Discussionsupporting
confidence: 81%
“…The results further confirm that migrant background is an independent determinant of health care use [8,9]. Interestingly, the difference between migrant groups and the general population in patterns of use was clear also when restricting the analysis to migrants who have stayed in Finland for at least 15 years, in contrast with finding that immigrants' treatment patterns would converge to those of the general population the longer they lived in Finland [66]. Previously, elderly Somalis have been demonstrated to use GP services at municipal health centers substantially more (90%) than native elderly Finns (34%) [67].…”
Section: Discussionsupporting
confidence: 61%
“…A register-based cohort study from Finland demonstrated that while the incidence and prevalence of mental disorders were overall lower among migrants compared with the native Finnish population, large risk differences emerged when examined by migrant origin and mental disorder group [ 19 ]. In addition, a recent register-based study in Finland showed less mental health service use among migrants than native Finnish controls, and that migrants from Eastern Europe, Middle East, and Africa have the highest risk of receiving low-intensity treatment [ 20 ]. Based on these separate studies, there appears to be a discrepancy between the observed high prevalence of mental health problems and the infrequent use of mental health services among people of migrant origin in Finland.…”
Section: Introductionmentioning
confidence: 99%